Galvanic Corrosion 1988
DOI: 10.1520/stp26195s
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tube-Tubesheet Galvanic Corrosion Using Finite Element and Wagner Number Analyses

Abstract: Galvanic corrosion predictions for heat exchanger tube/tubesheet galvanic couples are presented and discussed. The predictions were performed using finite element analysis using two programs, WECAN and MARC, and by Wagner number analysis under conditions of secondary and tertiary current distribution. Long-term electrochemical potentiostatic polarization data generated over 120 days in natural seawater were used to account for time effects. Results of the predictions are presented in the form of potential and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Finite element analysis (FEA) of potential and current distributions in galvanic systems has long been studied in the literature [21][22][23][24][25][26][27]. Such studies are often carried out to investigate fundamental effects of electrolyte geometry [26,28,29], electrode kinetics [25], and unique part geometries [21].…”
Section: International Journal Of Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite element analysis (FEA) of potential and current distributions in galvanic systems has long been studied in the literature [21][22][23][24][25][26][27]. Such studies are often carried out to investigate fundamental effects of electrolyte geometry [26,28,29], electrode kinetics [25], and unique part geometries [21].…”
Section: International Journal Of Corrosionmentioning
confidence: 99%
“…Such studies are often carried out to investigate fundamental effects of electrolyte geometry [26,28,29], electrode kinetics [25], and unique part geometries [21]. Early modeling attempts have provided an analytical solution [26,30] for the galvanic current and potential distribution around a galvanic junction involving two dissimilar metals kept side by side and covered by a corroding solution.…”
Section: International Journal Of Corrosionmentioning
confidence: 99%
“…It is usual to find carbon steel boxes and titanium, stainless steel, or even different copper alloy tubes and plates [2]. All these alloys have different electrochemical corrosion characteristics, and due to their electrical contact a galvanic corrosion can be induced [3]. In the event of cathodic protection, applied in the box, the plate is cathodically polarized, but its effect may not be seen by the entire tube and a part of it will work as an anode.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the electrolyte involves many factors such as pH, composition, concentration of the ions and the conductivity of the electrolyte. The influence of conductivity on galvanic corrosion has been studied in terms of "macroscopic" and "microscopic" galvanic cells [14], or in terms of the Wagner number [15,16]. Recent research revealed the complicated "alkalization", "passivation" and "poisoning" effects during the salt spray exposure which may be difficult to predict accurately using numerical methods [3].…”
Section: Introductionmentioning
confidence: 99%